INSIHGT: an accessible multi-scale, multi-modal 3D spatial biology platform - Chun Ngo Yau; Jacky Tin Shing Hung; Robert A. A. Campbell; Thomas Chun Yip Wong; Bei Huang; Ben Tin Yan Wong; Nick King Ngai Chow; Lichun Zhang; Eldric Pui Lam Tsoi; Yuqi Tan; Joshua Jing Xi Li; Yun Kwok Wing; et al. (Nature Communications)
Abstract Biological systems are complex, encompassing intertwined spatial, molecular and functional features. However, methodological constraints limit the completeness of information that can be extracted. Here, we report the development of INSIHGT, a non-destructive, accessible three-dimensional (3D) spatial biology method utilizing superchaotropes and host-guest chemistry to achieve homogeneous, deep penetration of macromolecular probes up to centimeter scales, providing reliable semi-quantitative signals throughout the tissue volume. Diverse antigens, mRNAs, neurotransmitters, and post-translational modifications are well-preserved and simultaneously visualized. INSIHGT also allows multi-round, highly multiplexed 3D molecular probing and is compatible with downstream traditional histology and nucleic acid sequencing. With INSIHGT, we map undescribed podocyte-to-parietal epithelial cell microfilaments in mouse glomeruli and neurofilament-intensive inclusion bodies in the human cerebellum, and identify NPY-proximal cell types defined by spatial morpho-proteomics in mouse hypothalamus. We anticipate that INSIHGT can form the foundations for 3D spatial multi-omics technology development and holistic systems biology studies.